﻿Therapy of post-COVID-19 syndrome: improving the efficiency and safety of basic metabolic drug treatment with tiazotic acid (thiotriazoline) - Igor Belenichev; Lyudmyla Kucherenko; Sergii Pavlov; Nina Bukhtiyarova; Olena Popazova; Natalia Derevianko; Ganna Nimenko (Pensoft Publishers, 2022)
COVID-19 leads to disruption of the blood coagulation system, to thrombosis, hypercoagulability, as a result, to an increased risk of strokes and heart attacks. During COVID-19, endothelial dysfunction develops associated with NO deficiency with decrease in the level of SH compounds. Tiazotic acid (Thiotriazoline) has immunomodulatory, anti-inflammatory, antioxidant, anti-ischemic, cardio- and endothelioprotective, antiplatelet, hepatoprotective activity. Our studies conducted at the National Research Medical Center "University Clinic of ZSMU" with the participation of 57 patients (from 30 to 65 years old) with post-COVID syndrome, who received thiotriazol with basic therapy in either tablets (200 mg each) or suppositories Dalmaxin (0.2 g each) twice a day for 30 days. Inclusion criteria for the study were a positive PCR test for COVID-19; if the PCR test was negative, then the presence of IgM COVID-19 or IgG COVID-19 (with radiologically confirmed pneumonia). The following biochemical parameters were studied: C-reactive protein - by immunoturbodimetric method; D-dimer - by enzyme immunoassay; ferritin - by immunochemiluminescent method; endothelial NO-synthase (eNOS) - by ELISA method; alanine aminotransferase (ALT), aspartate aminotransferase (AST), γ-glutamyltransferase (GGT), total bilirubin; international normalized ratio (INR) and determination of platelet aggregation. During treatment with thiotriazoline, significant increase in the eNOS content was recorded, which indicated the presence of endothelioprotective activity of the drug. Thiotriazoline significantly reduced the level of D-dimer in the blood of patients, and also led to the normalization of INR. The established effects testified to the presence of antiplatelet and fibrinolytic action of thiotriazoline and its ability to reduce the risks of heart attacks and strokes in post-COVID syndrome. Thiotriazoline led to an objective improvement in general clinical parameters in patients with post-COVID syndrome, complaints of palpitations disappeared, blood pressure stabilized.